2020
DOI: 10.21037/tau-20-498
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-related genes are potential diagnostic and prognostic biomarkers in prostate cancer

Abstract: Background: Recently, autophagy was found related to several malignances. Methods: To explore the diagnostic and prognostic values of autophagy in prostate cancer (PCa), we first identified differentially expressed autophagy-related genes (DEARGs) based on The Cancer Genome Atlas (TCGA) Prostate Adenocarcinoma (PRAD) dataset. Gene ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment were applied to perform gene functional annotation.Then, multivariate logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…These genes are responsible for autophagy regulation and subsequent impact on resistance of prostate cancer to platinum-containing compounds and EGFR tyrosine kinase inhibitors. Among them, five autophagy-related genes (ARGs) including ATG9B , DNAJB1 , HSPB8 , NKX2-3 and TP63 demonstrate remarkable association with prostate cancer development [ 446 ]. Further investigation demonstrates that autophagy can also be considered as a prognostic factor in prostate cancer.…”
Section: Autophagy and Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…These genes are responsible for autophagy regulation and subsequent impact on resistance of prostate cancer to platinum-containing compounds and EGFR tyrosine kinase inhibitors. Among them, five autophagy-related genes (ARGs) including ATG9B , DNAJB1 , HSPB8 , NKX2-3 and TP63 demonstrate remarkable association with prostate cancer development [ 446 ]. Further investigation demonstrates that autophagy can also be considered as a prognostic factor in prostate cancer.…”
Section: Autophagy and Prostate Cancermentioning
confidence: 99%
“…Further studies reveal an interaction between MIR205 and NKX2-3 that determines the therapy response of prostate cancer patients [ 452 ]. Therefore, autophagy and its related genes are potential biomarkers for prostate cancer diagnosis and prognosis [ 446 , 453 , 454 ]. Figure 9 provides a schematic representation of autophagy mechanism involvement in various aspects of prostate cancer from proliferation and metastasis to therapy resistance and prognostic signature.…”
Section: Autophagy and Prostate Cancermentioning
confidence: 99%
“…They identified sixteen DEARGs, and seven of them were associated with PCa overall survival (OS). Moreover, clinical characteristics were associated with three prognostic genes ( NPC1, BNIP3, TP53 ): the elevated expression of NPC1 (Niemann–Pick C1 protein) and BNIP3 (BCL2 Interacting Protein 3) was dramatically associated with advanced pathological T stages; in addition, overexpression of NPC1 was significantly related to higher ISUP grades [ 46 ]. Similarly, another study conducted by Hu and colleagues has evidenced more than twenty ARGs affecting disease-free survival (DFS) related to T status, N status, and Gleason score [ 47 ].…”
Section: Autophagy and Prostate Cancermentioning
confidence: 99%
“…In support of a possible role of autophagy in MM, it was reported that aberrant expression of autophagy-related genes is associated with cancer development [30] and that multiple activators of autophagy or specific autophagy-related genes are commonly found in cancer-associated regions [31]. Interestingly, it was also described that expression of autophagy-related genes influences the response to conventional treatments in MM [32][33][34] and, thereby, disease progression [35,36], arguing that they may be useful to predict disease risk [37]. However, despite these findings suggesting a key role of autophagy in the etiology of MM and the existence of a genetic component controlling this catalytic process in MM, so far only ULK4, ATG5, and CDKN2A polymorphisms have been suggested to have an impact on the risk of MM [38,39].…”
Section: Introductionmentioning
confidence: 98%